Pitfalls in counselling: the craniosynostoses. Issue 2 (February 1991) - Marini, R; Temple, K; Chitty, L; Genet, S; Baraitser, M
Abstract : We describe three families to highlight the variability of expression and penetrance that can occur in the craniosynostoses. In two of the families, gene carriers were only identified in retrospect by looking at photographs of other family members. In the third family, identical twins were initially thought to be discordant for sagittal craniosynostosis until early skull x rays were examined and both were found to be affected. The dilemmas faced when counselling these families are discussed.